Review of experimental techniques for impact property of adhesive bonds. (July 2020) - You, Min; Li, Ming-Bo; Yuan, You-Lu; Lin, Gao; Ma, Fu-Wei; Du, Ling-Feng; Tang, Shan-Jie
Abstract: Assessing the impact property of the adhesives and the joints requires specific suitable experimental methods. Especially the most of the adhesives are sensitive to the strain rate that they must have to meet when a load is applied abruptly on the adhesive and adhesively bonded joints. In general, the impact tests of adhesive joints are usually divided into three ranges including low, medium and high velocity. Sometimes a body in hypervelocity collides with another one is faster than the sound velocity. This document aims to review the experimental methods that have been previously undertaken in this field. Discussed research topics include the impact test methods for the adhesive joints under low, medium, high and hypervelocity. The standard impact tests for adhesive joints (involving both bonded blocks and strips) are typically test methods with low-velocity and they are discussed. In the medium-velocity range, the applications of drop weight, inertia wheel, wedge falling, servohydraulic and pneumatic test methods are presented. In the high-velocity range, the advance of Split-Hopkinson bar as a special apparatus conceived to test materials is reported. The final section describes two practical applications of adhesive joints impacted under hypervelocity.